Spatiotemporal variations of stratospheric aerosol size between 2002 and 2005 from measurements with SAGE III/M3M - F. Wrana; T. Deshler; C. Löns; L. W. Thomason; L. W. Thomason; C. von Savigny (Atmospheric Chemistry and Physics)
Stratospheric aerosol size distribution parameters are derived from the multiple-wavelength aerosol extinction retrievals of the SAGE III/M3M instrument (Stratospheric Aerosol and Gas Experiment III on the Russian satellite Meteor-3M) and analyzed for their evolution between 2002 and 2005. The broad wavelength spectrum of the measurements enables us to derive all three parameters within an assumed monomodal lognormal size distribution. The 2002–2005 stratospheric aerosol layer was mostly at close to background conditions but included three moderate-magnitude tropical volcanic eruptions (Ruang, Reventador, and Manam). The SAGE III/M3M instrument measured only at middle and high latitudes, but derived particle size distribution (PSD) parameters indicate a reduction in particle size and an increase in particle number concentration after all three eruptions. In addition to this likely volcanic effect on the PSD, an influence of seasonal polar winter condensation events including meteoric smoke particles on the derived aerosol size is possible, especially due to the long-lasting low stratospheric temperatures during the northern winters of 2002/2003 and 2004/2005. During the same winters, polar stratospheric clouds (PSCs) were likely observed by the instrument. A comparison of the derived stratospheric aerosol size dataset with balloon-borne in situ measurements in Kiruna, Sweden, shows generally good agreement, but there are systematic differences below roughly 15 km altitude. Finally, the effect of the necessary assumption of a PSD shape on the aerosol size derivation with remote sensing instruments is shown and discussed.